The Fall of the Berlin Wall – 25 years on. (September 2014) - Lees, Charles
<x xml:space="preserve">Abstract</x> The events of 9 November 1989 changed the face of Europe. Two and half decades on from the fall of the Berlin Wall, Charles Lees evaluates the consequences of German unification for its economy, its domestic politics, and its role in the world. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>